Cotton-harvester-flow simulator for testing cotton yield monitors - Sui, Ruixiu; Thomasson, J. Alex; To, S. D. Filip (International Journal of Agricultural and Biological Engineering, 2010)
An experimental system was developed to simulate the pneumatic flow arrangement found in picker-type cotton harvesters. The simulation system was designed and constructed for testing a prototype cotton yield monitor developed at Mississippi State University. The simulation system was constructed to approximate the pneumatic cotton flow system of a cotton picker, and was capable of operating with varying cotton flow rates. The simulator was tested with different cotton flow rates, and the relationship between feeder rate and amount of conveyed seed cotton was found to be consistent. Further, the simulator was used to conduct tests with the novel optical cotton yield monitor, which proved accurate at measuring the amount of seed cotton flowing through the simulator. Finally, some differences between laboratory testing and field-testing were noted: seed cotton becomes fluffed and twisted when recycled through the simulator, and seed cotton stored in the laboratory tends to be of lower moisture content than cotton during harvest. These differences should be considered when using a laboratory simulator to test cotton yield monitors. Keywords: cotton yield monitor, precision agriculture, sensor, cotton harvester DOI: 10.3965/j.issn.1934-6344.2010.01.0-0 Citation: Ruixiu Sui, J. Alex Thomasson, S. D. Filip To. Cotton-harvester-flow simulator for testing cotton yield monitors. Int J Agric & Biol Eng, 2010; 3(1): <span style="line-height: 140%; font-family: